Specific Patterns of Canine Scavenging in Indoor Settings. Issue 2 (10th February 2015) - Colard, Thomas; Delannoy, Yann; Naji, Stephan; Gosset, Didier; Hartnett, Kristen; Bécart, Anne
Abstract Postmortem animal mutilations due to domestic dogs in isolated domestic deaths are taphonomic modifications regularly observed by forensic pathologists. They are rarely described in the literature; however, even though they present specific patterns. Through 41 cases, 10 at the forensic institute in Lille (France) and 31 at the New York City Office of Chief Medical Examiner (USA), plus 22 cases from the literature, specific locations and patterns of postmortem scavenging lesions are proposed. These lesions are mainly distributed in three locations: the face, especially the nose and the mouth (73.1%), the neck (43.1%), and the arm (shoulder/upper limb [29.2%], hand [26.8%]). We discuss the time span between death and scavenging, the consequences on identification, and comparison with outdoor settings. Outdoor scavenging lesions are mainly located on the trunk and limbs usually sparing the head, which strongly differs from indoor distribution and imply different animal motivations.